Age exacerbates the effect of myopia on retinal capillaries and string vessels - Lin, Carol Ren; Toychiev, Abduqodir; Ablordeppey, Reynolds Kwame; Srinivas, Miduturu; Benavente-Perez, Alexandra (Frontiers in Medicine, 2023)
The retinal vasculature supplies oxygen and nutrition to the cells and is crucial for an adequate retinal function. In myopia, excessive eye growth is associated with various anatomical changes that can lead to myopia-related complications. However, how myopia-induced ocular growth affects the integrity of the aged retinal microvasculature at the cellular level is not well understood. Here, we studied how aging interacts with myopia-induced alteration of the retinal microvasculature in fourteen marmoset retinas (Callithrix jacchus). String vessel and capillary branchpoint were imaged and quantified in all four capillary plexi of the retinal vasculature. As marmosets with lens-induced myopia aged, they developed increasing numbers of string vessels in all four vascular plexi, with increased vessel branchpoints in the parafoveal and peripapillary retina and decreased vessel branchpoints in the peripheral retina. These myopia-induced changes to the retinal microvasculature suggest an adaptive reorganization of the retinal microvascular cellular structure template with aging and during myopia development and progression.